For the base of the triangle, let's call it "b", we are given that it is four less than three times the height, so we can write it as:
b = 3h - 4
Now, let's substitute the value of the base in the formula for the area of the triangle:
Area = (b * h) / 2
Area = ((3h - 4) * h) / 2
To solve for h, let's first distribute the multiplication:
Area = (3h^2 - 4h) / 2
Now, let's rearrange the equation to isolate h:
2 * Area = 3h^2 - 4h
Rearranging the equation further:
3h^2 - 4h - 2 * Area = 0
Now, we have a quadratic equation that we can solve using the quadratic formula:
h = (-b ± sqrt(b^2 - 4ac)) / (2a)
In this case:
a = 3, b = -4, c = -2 * Area
Solving for h using the quadratic formula will give us the two possible values for the height.
The base of a triangle is four less than three times the height. The area of the triangle is 38 square centimeters. A=(b×h)2
for the base of the triangle: Response area
Equation for the area of the triangle, substituting in for the base: Response area
The first step in solving for h: Response area
9 answers
whats the resposes for the blank
For the equation for the area of the triangle, substituting in for the base, the response should be:
Area = ((3h - 4) * h) / 2
And for the first step in solving for h, the response should be:
2 * Area = 3h^2 - 4h - 2 * Area = 0
Area = ((3h - 4) * h) / 2
And for the first step in solving for h, the response should be:
2 * Area = 3h^2 - 4h - 2 * Area = 0
what about the first one?
Apologies for the oversight. For the first step in solving for h, the response should be:
b = 3h - 4
b = 3h - 4
for the base of the triangle: Response area
Equation for the area of the triangle, substituting in for the base: Response area
The first step in solving for h: Response area
pls
Equation for the area of the triangle, substituting in for the base: Response area
The first step in solving for h: Response area
pls
I apologize for the confusion. Here are the correct responses:
For the base of the triangle: Let's call it "b".
Equation for the area of the triangle, substituting in for the base:
Area = (b * h) / 2
Substituting the value of the base into the equation:
Area = ((3h - 4) * h) / 2
The first step in solving for h:
To solve for h, we need to rearrange the equation:
2 * Area = (3h - 4) * h
I apologize for any confusion caused by the incorrect responses before.
For the base of the triangle: Let's call it "b".
Equation for the area of the triangle, substituting in for the base:
Area = (b * h) / 2
Substituting the value of the base into the equation:
Area = ((3h - 4) * h) / 2
The first step in solving for h:
To solve for h, we need to rearrange the equation:
2 * Area = (3h - 4) * h
I apologize for any confusion caused by the incorrect responses before.
i dont have that option for the first one
Apologies for the confusion. Here are the correct responses:
For the first blank, the correct response is:
For the base of the triangle: Let's call it "b".
For the equation for the area of the triangle, substituting in for the base, the correct response is:
Area = (b * h) / 2
And for the first step in solving for h, the correct response is:
b = 3h - 4
For the first blank, the correct response is:
For the base of the triangle: Let's call it "b".
For the equation for the area of the triangle, substituting in for the base, the correct response is:
Area = (b * h) / 2
And for the first step in solving for h, the correct response is:
b = 3h - 4